IMPLEMENTASI JALUR PENDAFTARAN PERATURAN MENTERI PENDIDIKAN DAN KEBUDAYAAN NOMOR 44 TAHUN 2019 TENTANG PENERIMAAN PESERTA DIDIK BARU PADA JENJANG SEKOLAH MENENGAH ATAS DI KECAMATAN TAMPAN KOTA PEKANBARU - Heldayati Heldayati; Sri Erlinda; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The background of this research is that there are obstacles in the availability of public schools that are not evenly distributed, but the zoning rules require students to register at the school closest to their homes. The unequal number of state schools is exacerbated by the unbalanced ratio of the capacity of secondary schools to graduates from primary schools. Implementation of the New Student Admission system at the high school level in Tampan District, Pekanbaru City, Riau Province. In the 2020/2021 Academic Year, registration has been implemented through 4 main channels, namely zoning, affirmation, transfer of parents/guardians and achievement, which slightly differed in New Student Admissions in previous years. As for the formulation of the problem in this study How is the Implementation of the Registration Path Permendikbud No. 44 of 2019 concerning Admission of New Students to Senior High Schools in Tampan District, Pekanbaru City. This study aims to determine the implementation of the Registration Path for the Minister of Education and Culture Regulation Number 44 of 2019 concerning PPDB at the High School Level in Tampan District, Pekanbaru City. This research method is descriptive quantitative. The population in this study amounted to 975 people, using a purposive sampling technique totaling 181 people. Based on the results of the study, it can be concluded that the Implementation of the Registration Track for the Regulation of the Minister of Education and Culture Number 44 of 2019 concerning Admission of New Students at the High School Level in the Tampan District of Pekanbaru City can be said to have been "well implemented”Key Words: New Student Admission